Research on the influence mechanism of digitalization degree on manufacturing enterprise performance - WANG, Dandan (Institutional Knowledge at Singapore Management University, 2024)
The application of digital technologies has changed the operation model of traditional industries, and promoted the development of emerging industries. More and more manufacturing enterprises have started or completed digital transformation, and tried new ways of development. With the advancement of digitalization, the influence of the degree of digitalization on high-quality economic development has attracted great attention from scholars at home and abroad. Although significant resources are put into digital transformation, which is deemed as a strategic core, the specific influence paths of the degree of digitalization on enterprise performance have not yet been fully explored. In the digital era, the market environment on which enterprises depend for survival has become more complex. The dynamic capabilities theory (DCT) provides an applicable theoretical perspective for analyzing the relationship between enterprises' digital transformation and their performance. In manufacturing industry, dynamic capabilities are often considered to be a critical factor. Enterprises with stronger dynamic capabilities are more likely to gain the upper hand in a fiercely competitive market and sustain their growth and edges. The use of digital technologies can accelerate enterprises' perception capability of the external environment, increase access channels to resources and information, and propel them to quickly integrate resources according to changes in the external environment, thus improving their performance. This study based on DCT and with empirical research methods, dynamic capabilities are selected as mediating variables and innovation orientation and degree of environmental turbulence as moderating variables to build a research model and put forward research hypotheses. With a sample of manufacturing enterprises in Jiangsu and Zhejiang Provinces of China, this study obtains statistical analysis data through questionnaire survey, and uses maturity scales to ensure the reliability. Finally, through the empirical statistical analysis method and software such as SPSS 23.0 and Mplus 8, the author, based on the data collected with the scales, verifies the model built and the hypotheses put forward, and explores the influence path of the degree of digitalization on manufacturing enterprise performance. The results of empirical analysis show that: (1) The degree of enterprise digitalization is positively correlated with enterprise performance; (2) Dynamic capabilities play a mediating role between the degree of enterprise digitalization and enterprise performance; (3) Innovation orientation plays a positive moderating role in the relationship between the degree of enterprise digitalization and dynamic capabilities; (4) The degree of environmental turbulence plays a positive moderating role in the relationship between enterprise performance and dynamic capabilities.